2019
DOI: 10.1186/s12883-019-1389-0
|View full text |Cite
|
Sign up to set email alerts
|

Acquired epileptiform opercular syndrome evaluated with real-time transcranial Doppler ultrasound-video-electroencephalogram before and after treatment: a case report

Abstract: Background Acquired epileptiform opercular syndrome (AEOS) with electrical status epilepticus during sleep (ESES) may be recurrent and intractable. The real-time transcranial Doppler ultrasound–sleep-deprived video electroencephalogram (TCD-SDvEEG) can be used to observe the relationships among hemodynamic, electrophysiological, and clinical factors in a patient during therapy. This study reported the case of a healthy 5-year-old boy with AEOS. Case presentation The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Consequently, continuous and active treatment of seizures, SES, and neuropsychological impairments in children with ABFEC is highly essential. Moreover, our previously reported findings [20,21] suggested that clinical symptoms of CI in IFE patients might be improved when EEG was transformed from comprehensive at initial examination to focal or multifocal at later investigation. Therefore, seizure control and cognitive improvement mainly coexisted in children with SES.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Consequently, continuous and active treatment of seizures, SES, and neuropsychological impairments in children with ABFEC is highly essential. Moreover, our previously reported findings [20,21] suggested that clinical symptoms of CI in IFE patients might be improved when EEG was transformed from comprehensive at initial examination to focal or multifocal at later investigation. Therefore, seizure control and cognitive improvement mainly coexisted in children with SES.…”
Section: Discussionmentioning
confidence: 90%
“…The therapeutic outcome measures were based on the EEG outcomes as well as clinical response. The decrement of more than 25% in SWI, or transformation of generalized continuous activity into focal continuous activity, was considered as EEG improvement [20,21]. However, in terms of SES pattern being focal or multifocal pattern [22] at initial examination, the EEG improvement was based on the decrement of more than 25% in SWI.…”
Section: Outcome Measuresmentioning
confidence: 99%